Determinants of Music Development and the Influence of Music Education on Overall Personal Development - Bozana Raskovic,; Popović, Daliborka (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The development of musical abilities and the space given to music education is determined by various factors. Disagreement in opinions about the role of some factors carries the danger of neglecting some activities that would contribute to the development of musical talent. In that sense, the aim of the paper is pointed at understanding the importance of hereditary and environmental factors for the development of musical abilities, with special emphasis on determining the activities of adults in the function of music education and achievement, but also overall development. Applying the method of theoretical analysis, a comparison of different conceptual approaches was performed, as well as of the results of the conducted research and the conclusions of the authors. After considering these issues, it is concluded that although debates about giving preference to certain factors still exist, there is no dilemma that innate and environmental factors are both important, but not in themselves without the activities of an individual. Accordingly, the role of parents, educators, and teachers in motivating and provoking children's musical development with adequate musical content, overall communication, and atmosphere was emphasized. The pedagogical implications are contained in the above recommendations for the correct approach in creating musical content and a stimulating environment. Future research should be focused on examining and possibly improving the competencies of professionals—educators and teachers—to discover and support musically gifted children
Keywords: musical abilities; inheritance; environment; music education; adult support